2008
DOI: 10.1007/s00402-008-0742-3
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of a 17-year long-term bisphosphonate therapy in a patient with Gorham–Stout syndrome

Abstract: This case report of a 61-year-old woman suffering from Gorham-Stout syndrome shows osteolyses of the left pelvis, proximal femur and lumbar spine. The therapeutic regime has included two courses of percutaneous radiotherapy and also continuous application of bisphosphonates over 17 years. Despite this antiresorptive therapy, elevated urinary excretion of desoxypyridinoline has indicated the persistence of increased bone destruction. The radiological progression following bisphosphonate treatment was only moder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
6

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 21 publications
2
37
1
6
Order By: Relevance
“…Bisphosphonate is helpful because of its putative antiosteoclastic and anti-angiogenic activity. Lehmann et al (2009) reported that a case of GSS was successfully treated with bisphosphonates for more than 17 years. Hammer et al (2005) reported that mono-therapy with bisphosphonates (30 mg intravenous every three months) controlled the disorder during two years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Bisphosphonate is helpful because of its putative antiosteoclastic and anti-angiogenic activity. Lehmann et al (2009) reported that a case of GSS was successfully treated with bisphosphonates for more than 17 years. Hammer et al (2005) reported that mono-therapy with bisphosphonates (30 mg intravenous every three months) controlled the disorder during two years of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Heyd et al reported a 77% to 80% success rate of radiotherapy, and recommended a total dose ranging from 36 to 45 Gy (Heyd et al 2011a). As for chemotherapy, bisphosphonates (Lehmann et al 2009) and interferon α-2b (Hagberg et al 1997) have most commonly been used. Other pharmaceuticals, including the anti-VEGF-A antibody (Grunewald et al 2010), propranolol (Nir et al 2014), low molecular weight heparin (Brodszki et al 2011), and rapamycin (Hammill et al 2011), have also been tested experimentally.…”
Section: Discussionmentioning
confidence: 99%
“…The precise etiology and pathophysiology of the disease remain poorly understood (Lehmann et al 2009;Dellinger et al 2014). Furthermore, due to uncertainty about the underlying cause, the appropriate treatment and prognosis currently remain uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Мнения о роли остеокластов в деструкции костной ткани при GSD противоречивы: ряд исследователей подтверждает их высокую активность [1,5,6,18,22,26,32,36,42,44,48,50], другие отмечают их отсутствие в оча-гах остеолиза [12,13,21,45,51]. При-чина такого противоречия, возмож-но, обусловлена проведением гисто-логического исследования на разных стадиях процесса [4].…”
Section: рисunclassified